Johan Galtung's Theory of Violence and Conflict: A Study of Pela Gandong's Local Wisdom as a Media for Conflict Resolution in Ambon - Muhammad Riyyan Firdaus; Neneng Gina Agniawati; M. Solahudin (Gunung Djati Conference Series, 2021)
This study aims to discuss conflict theory in the perspective of Johan Galtung and local wisdom Pela Gandong as a media for conflict resolution in Ambon. This research method is qualitative through literature study. The results and discussion of this research include conflict theory, violence theory, and Pela Gandong local wisdom as conflict resolution in Ambon. This study concludes that Ambonese people have a local wisdom that can overcome conflicts that occur, whether they have ethnic, religious, racial, and inter-group nuances or not, namely the local wisdom of pela gandong which offers peaceful conflict resolution and creates harmony in society. or at least can reduce the occurrence of violence.